HUBUNGAN MOTIVASI DENGAN PRODUKTIVITAS KERJA PEGAWAI DI KANTOR BALAI BESAR PENDIDIKAN DAN PELATIHAN KESEJAHTERAAN SOSIAL REGIONAL I SUMATERA - RAHMAYANI RAHMAYANI (Universitas Negeri Padang, 2016)
This research aim to get information and data about work produktivity, motivation and the correlation motivation with productivity work. Population are 45 people and sample are 32 people by using formulate Cochran with stratified random sampling technique. Instrument used a scale of Likert. The techhique of data analysis the statistically use correlation technique by assist program computer of SPSS 16.0 for windows. The result of research indicate that 1) Work productivity reside in good category 81,64 %. 2) Motivation reside in enough category 76,85%, 3) there was a significant correlation between motivation and work productivity equal to 0,490.